Family Social Support and Behavior of Children with Caries in Doing Dental and Oral Care - Indrianingsih, Nurfaida; Prasetyo, Yoyok Bekti; Kurnia, Anggraini Dwi (Jurnal Keperawatan, 2018)
Social support is an interpersonal relation which one individual provides support to another individual. The aim of this study was to examine the correlation of family support and behavior of 4 - 6 years old in doing dental and oral care. The research method used correlation research with quantitative approach. The participants of this reseach were 62 families who have children aged 4 to 6. The data analysis used Spearman Rank (Rho) correlation test that is carried out to discover the correlation between family support and behavior of 4 - 6 years old in doing dental and oral care. The resultÂ  showed that P= 0,027. It can be concluded that there is a relationship between family support and the behavior of children aged 4-6 years in performing dental and oral health care.